A Study on Food and Wine Pairing of Blooms Restaurant, Eros Hotel, Nehru Place (Global Journal of Management and Business Research, 2022)
Appropriate wine selection and food pairings provide caterers with opportunities to increase customer gastronomic satisfaction as part of the dining experience. This paper discusses objectives in food and wine pairing, matching traditions, and key elements of wine and food: components, texture, and flavors. The practice is designed to provide students and guests with an increased depth of experience in food and wine pairing and knowledge of how food and wine elements interact and transform one another. The aim of this study was to identify which attributes impacted the dynamic liking food and wine individually, as well as when consumed together. A good pairing is based on the complementary role of wine on the four important factors of food: components, textures, flavors and colors. Common wine and food examples of food preparation with wine or vine products, such as grapes or vine leaves.